THE EXPERIENCE OF TREATMENT OF PATIENTS WITH ULCER DISEASE WITH ASSOCIATED CHRONIC DUODENAL INSUFFICIENCY - Ya. M. Vakhrushev; M. S. Busygina; O. V. Danilova (SINAPS LLC, 2017)
Objective: study of the efficacy of tiotyprid hydrochloride in the complex therapy of patients with gastric ulcer and duodenal ulcer with concomitant chronic duodenal insufficiency. Materials and methods. Verification of ulcer disease was performed clinically and by fibrogastroduodenoscopic researches. In determination of chronic duodenal insufficiency there were used data of contrast duodenography and cavitary manometry. We have studied motor performance of the stomach and gastroduodenal ulcer with a help of peripheral electrogastrograph ЭГГ-4М. The protective properties of gastric mucus were determined by using the Sialo Test reagent kit. Gastrin, cortisol, insulin in the blood serum were studied with a help of method ELISA. Results of the study. We have carry out complex examination of 104 patients with ulcer disease which were divided into 2 groups. The 1st group consisting of 52 patients with gastric ulcer with concomitant HDN was given in the complex therapy prokinetic taupoide hydrochloride in dose of 50 mg 3 times a day for 2 weeks. The 2st group in the number of 52 patients with gastric ulcer with concomitant HDN received only standard anti-ulcer therapy. With a comparative evaluation of the effectiveness of therapy in patients 1 gr. established, in addition to the positive dynamics of clinical symptoms, a distinct improvement in the motor activity of stomach and duodenum, the restoration of the gatekeeper's closure function, and the enhancement of protective and protective properties of gastric mucus. The scarring of ulcer was revealed in 97,4 ± 1,8% of patients of 1 group, in 87,1 ± 0,41% cases in the stage of mature "white rumen" (S2). In patients 2 group the scarring of the ulcer occurred in 92.1 ± 3.1% of cases, but in 41 ± 4.3% of cases, ulceration was substandard, that is, in the "red scar" stage (S1). Conclusion. The using of prokinete ticopride hydrochloride in the complex treatment of gastric ulcer with concomitant HDN is pathogenetically substantiated and clinically effective.